2017
DOI: 10.5965/223811711612017048
|View full text |Cite
|
Sign up to set email alerts
|

Controle de plantas daninhas e aspectos produtivos de morangueiro sob diferentes coberturas do solo

Abstract: RESUMOEste trabalho teve o objetivo de avaliar a produtividade do morangueiro em função de diferentes coberturas de solo e a efetividade destas sobre o controle de plantas daninhas, em sistema orgânico de produção. O experimento foi conduzido em área da Universidade Federal da Fronteira Sul -UFFS, Campus Cerro Largo. Utilizou-se delineamento de blocos ao acaso com seis blocos. Cada parcela foi constituída por dez plantas da cultivar Aromas, dispostas em quatro linhas intercaladas, distanciadas em 0,30 metros. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Using different types of cover crops, Resende et al (2005) and Santos et al (2011) also reported an increased carrot crop yield of, in average, 32 and 13%, respectively. In other crops, such as lettuce (Lactuca sativa L.) and strawberry [Fragaria × ananassa (Weston) Duchesne ex Rozier], the use of soil cover provided gains of 32 and 2.5% in commercial yield, respectively (Barbosa et al, 2018;Tonin et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Using different types of cover crops, Resende et al (2005) and Santos et al (2011) also reported an increased carrot crop yield of, in average, 32 and 13%, respectively. In other crops, such as lettuce (Lactuca sativa L.) and strawberry [Fragaria × ananassa (Weston) Duchesne ex Rozier], the use of soil cover provided gains of 32 and 2.5% in commercial yield, respectively (Barbosa et al, 2018;Tonin et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the use of quality seedlings implies less need for applications of substances to control diseases and pests. The conventional system with the use of agrochemicals is still the main form of production in the crop and it is estimated that only 1% of the cultivated area in the country is destined for organic production (TONIN et al, 2017;DAROLT, 2008).…”
Section: Introductionmentioning
confidence: 99%